2020
DOI: 10.3390/nu12030638
|View full text |Cite
|
Sign up to set email alerts
|

Energy Restriction Enhances Adult Hippocampal Neurogenesis-Associated Memory after Four Weeks in an Adult Human Population with Central Obesity; a Randomized Controlled Trial

Abstract: Adult neurogenesis, the generation of new neurons throughout life, occurs in the subventricular zone of the dentate gyrus in the human hippocampal formation. It has been shown in rodents that adult hippocampal neurogenesis is needed for pattern separation, the ability to differentially encode small changes derived from similar inputs, and recognition memory, as well as the ability to recognize previously encountered stimuli. Improved hippocampus-dependent cognition and cellular readouts of adult hippocampal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 74 publications
1
43
0
3
Order By: Relevance
“…8). These memory improvements were in line with previous DR studies in which DR (1) improves memory in adults [150] and older adults [45], (2) protects against hippocampal-dependent memory deficits and accumulations of hippocampal amyloid β-peptide plaques and neurofibrillary tangles in Alzheimer's disease model of mice [76], and (3) rejuvenates hippocampal transcriptome profiles in middle-aged mice [151]. Additionally, similar to our present findings, Li et al (2013) [73] showed that 11-month long EOD fasting in CD-1 wild-type male mice produced time-dependent memory enhancements.…”
Section: Discussionsupporting
confidence: 92%
“…8). These memory improvements were in line with previous DR studies in which DR (1) improves memory in adults [150] and older adults [45], (2) protects against hippocampal-dependent memory deficits and accumulations of hippocampal amyloid β-peptide plaques and neurofibrillary tangles in Alzheimer's disease model of mice [76], and (3) rejuvenates hippocampal transcriptome profiles in middle-aged mice [151]. Additionally, similar to our present findings, Li et al (2013) [73] showed that 11-month long EOD fasting in CD-1 wild-type male mice produced time-dependent memory enhancements.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this could indicate that IF might primarily have positive effects on cognition later in life when insulin sensitivity and glucose metabolism decays. However, Kim and colleagues did not find any differences of improvement in neurogenesis-associated memory after a PF diet between healthy younger subjects (from 35 years old) and healthy older subjects (till 75 years old) [153]. In addition, Brandhorst and colleagues also did not find age differences on reduced risk factors for age-related diseases and stroke vulnerability in healthy subjects after a 3-month FMD compared to a control group [146].…”
Section: If Initiated In Different Age Groupsmentioning
confidence: 95%
“…There are more studies that report indications of a reduced risk for neurological diseases due to IF in healthy people. For instance, lowered APP levels [74], enhanced hippocampal neurogenesis [153] and decreased mTOR pathway activity [21], which are all protective of developing AD [154]. An interesting translational effort was done by Brandhorst et al, 2015, where middle aged mice (20 months) and 38 human adults (age 20 -68 years) followed a FMD protocol.…”
Section: If Initiated In Different Age Groupsmentioning
confidence: 99%
“…Calorie restriction (CR), typically defined as a 10-40% total reduction in daily calorie intake, and intermittent fasting (IF), typically involving every-other-day feeding, are two established dietary paradigms that extend life-and healthspan across species [1][2][3][4][5]. A recent study demonstrated that adoption of 30% CR or a single meal feeding strategy for 10 months enhanced longevity and health status in mice, regardless of whether their content was high or low in sugar [6].…”
Section: Introductionmentioning
confidence: 99%